Molecular dynamics simulation and structural analysis of aquaporin Z from an Antarctic Pseudomonas sp. strain AMS3 - Balakrishnan, S.; A. Rahman, R. N. Z. R.; M. Noor, N. D.; Latip, W.; M. Ali, M. S. (Taylor and Francis Group, 2023)
Aquaporin is a water channel protein that facilitates the movement of water across the cell membrane. Aquaporin from the Antarctic region has been noted for its psychrophilic properties and its ability to perform at a lower temperature but there remains limited understanding of the water mechanism of Antarctic Pseudomonas sp. strain AMS3 However, studies regarding aquaporin isolated from psychrophilic Pseudomonas sp. are still scattered. Recently, the genome sequence of an Antarctic Pseudomonas sp. strain AMS3 revealed a gene sequence encoding for a putative aquaporin designated as AqpZ1 AMS3. In this study, structure analysis and a molecular dynamics (MD) simulation of a predicted model of a fully hydrated aquaporin tetramer embedded in a lipid bilayer was performed at different temperatures for structural flexibility and stability analysis. The MD simulation results revealed that the structures were able to remain stable at low to medium temperatures. The protein was observed to have high flexibility in the loop region as compared to the helices region throughout the simulated temperatures. The selectivity filter and NPA motifs play a major role in solute selectivity and the pore radius of the protein. The structural and functional characterization of this psychrophilic aquaporin provides new insights for the future applications of this protein.